PENGARUH STRUKTUR MODAL, LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Study kasus pada perusahaan Manufaktur Sub sektor Makanan dan Minuman yang terdaftar di BEI pada tahun 2015-2017) - Nifta Asfidza Alma; Ronny Malavia Mardani; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe purpose of this research is to determine the effect of capital structure, liquidity and profitability on the value of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2015-2017. The independent variables in this study are capital structure, liquidity and profitability while the dependent variable is firm value. The analytical method used is multiple linear regression. The results of sampling using Purposive sampling and that meets the criteria sample of 14 manufacturing companies obtained by searching for and collecting annual report data obtained from the website. To overcome the problem in this study is to use the normality test, classic assumption test, multiple linear regression test and hypothesis test. Based on the results of testing hypotheses conducted, it can be concluded that the capital structure (DER) has no significant negative effect on firm value, Liquidity (CR) has a significant positive effect on firm value and Profitability (ROE) has a positive influence. and does not have a significant effect on the value of the food and beverage sub-sector manufacturing companies in the period 2015-2017.Keywords: company value, capital structure, liquidity, profitability